Nurses and subordination: a historical study of mental nurses' perceptions on administering aversion therapy for 'sexual deviations'. Issue 4 (22nd July 2013) - Dickinson, Tommy; Cook, Matt; Playle, John; Hallett, Christine
<x xml:space="preserve">Abstract</x> This study aimed to examine the meanings that nurses attached to the 'treatments' administered to cure 'sexual deviation' (SD) in the UK, 1935–1974. In the UK, homosexuality was considered a classifiable mental illness that could be 'cured' until 1992. Nurses were involved in administering painful and distressing treatments. The study is based on oral history interviews with fifteen nurses who had administered treatments to cure individuals of their SD. The interviews were transcribed for historical interpretation. Some nurses believed that their role was to passively follow any orders they had been given. Other nurses limited their culpability concerning administering these treatments by adopting dehumanising and objectifying language and by focussing on administrative tasks, rather than the human beings in need of their care. Meanwhile, some nurses genuinely believed that they were acting beneficently by administering these distinctly unpleasant treatments. It is envisaged that this study might act to reiterate the need for nurses to ensure their interventions have a sound evidence base and that they constantly reflect on the moral and value base of their practice and the influence that science and societal norms can have on changing views of what is considered 'acceptable practice'.